PERANCANGAN SISTEM INFORMASI AKADEMIK PADA SEKOLAH DASAR ISLAM TERPADU (SDIT) AS-SHIDIIQI JAMBI BERBASIS WEB - Lailyn Puad (JURNAL AKADEMIKA)
The process of academic data at the integrated islam elementary school AS-Shidiiqi Jambi have used computer system but it has not felt optimal yet, because it has been formed in a hardcopy, therefore it perhamps a redudandy or lost and damaged data that will make the academic data processing and data searching have too much of time. Schools are institutions of formal education in Indonesia, it really important to educate the youth of nation. The information system is one of the most important system that can be very usefull for school, which is a media to interact with society to knowing information about school. Purpose of this study is to making a software that able to serve information also helping the school in data processing and served information to the society.